EURRECA nutritional planning and dietary assessment software tool: NutPlan - Gurinovic, M. (2010)
Approaches through which reference values for micronutrients are derived, as well as the reference values themselves, vary considerably across countries. Harmonisation is needed to improve nutrition policy and public health strategies. The EURRECA (EURopean micronutrient RECommendations Aligned, http://www.eurreca.org) Network of Excellence is developing generic tools for systematically establishing and updating micronutrient reference values or recommendations. Different types of instruments (including best practice guidelines, interlinked web pages, online databases and decision trees) have been identified. The first set of instruments is for training purposes and includes mainly interactive digital learning materials. The second set of instruments comprises collection and interlinkage of diverse information sources that have widely varying contents and purposes. In general, these sources are collections of existing information. The purpose of the majority of these information sources is to provide guidance on best practice for use in a wider scientific community or for users and stakeholders of reference values. The third set of instruments includes decision trees and frameworks. The purpose of these tools is to guide non-scientists in decision making based on scientific evidence. This platform of instruments will, in particular in Central and Eastern European countries, contribute to future capacity-building development in nutrition. The use of these tools by the scientific community, the European Food Safety Authority, bodies responsible for setting national nutrient requirements and others should ultimately help to align nutrient-based recommendations across Europe. Therefore, EURRECA can contribute towards nutrition policy development and public health strategies.